The Microbial Diversity of Cabbage Pest Delia radicum Across Multiple Life Stages - van den Bosch, Tijs J. M.; Welte, Cornelia U. (Frontiers in Microbiology, 2020)
The cabbage root fly Delia radicum is a worldwide pest that causes yield losses of many common cabbage crops. The bacteria associated with D. radicum are suggested to influence the pest status of their host. In this study, we characterized insect-associated bacteria of Delia radicum across multiple life stages and of their diet plant (turnip, Brassica rapa subsp. rapa) by sequencing the V3-V4 region of 16S rRNA genes using the Illumina MiSeq platform. In total, over 1.2M paired-end reads were obtained, identifying 1006 bacterial amplicon sequence variants (ASVs) in samples obtained from the eggs, larvae, pupae and adults of Delia radicum, as well as turnips that were either fresh or infested with D. radicum larvae. The microbial community in Delia radicum was dominated by Wolbachia, a common endosymbiont of arthropods which we found in all of the investigated insect samples, with the pupal stage having the highest relative abundance. Moderate amounts of Firmicutes were found only in adult D. radicum flies, but not in previous life stages. Actinobacteria were mostly found on the eggs and on the skin of fresh plants on which the eggs were deposited. These plants also harbored a large amount of Pseudomonas. The bacterial diversity of the healthy turnip was low, whereas the microbial community of decaying turnips that were heavily infested by D. radicum larvae and showing symptoms of advanced soft rot was characterized by a high bacterial diversity. Taken together, this work provides insights into the bacterial communities associated with the cabbage pest Delia radicum and its associated disease symptoms.